THE LINGUISTIC CREATIVITY AND ITS IMPACT ON LOCAL ECONOMIC POTENTIAL AND GLOBAL INCOME - Vivi Nansy Tumuju; Mercy Mantau; Tien Siamando (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the linguistic creativity in the naming practices of restaurants in Manado, Indonesia, focusing on the influence of local culture, language, and global trends. The research analyzes a sample of 230 restaurant names to explore the types of languages used, including Indonesian, local dialects, foreign languages, and hybrid combinations. The findings show that Indonesian names dominate the market, making up 51.3% of the total sample, followed by foreign language names at 16.1%, and local dialect names at 12.2%. Hybrid names combining local and foreign elements account for 32.2% of the total, reflecting a blending of local and global influences in Manado's culinary scene. The study also explores the use of linguistic strategies such as wordplay, alliteration, and metaphors, highlighting their role in shaping brand identities and consumer perceptions. These creative strategies not only enhance brand recall but also serve as powerful tools for differentiation in a competitive market. The research emphasizes the significance of cultural and regional factors in shaping naming trends, with local dialects and cultural references playing a central role in creating authentic and relatable brands. It also compares the naming practices in Manado with those in other regions, suggesting that while global influences are present, the local culture remains a key element in restaurant branding. The paper concludes with practical implications for restaurant owners and marketers, providing insights into effective naming strategies to attract and engage customers. The study further identifies limitations, such as its sample size and geographic scope, and suggests areas for future research, including expanding the study to other cities or focusing on specific restaurant types.